Pemanfaatan Kelapa sebagai Minyak di Desa Hargotirto, Kecamatan Kokap, Kulon Progo, Yogyakarta - Lukisworo, Agustinus Aryo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Kuliah Kerja Nyata (KKN) 79 started from April to May 2021 and was held online. In this period of KKN, LPPM distributed all the units into two main area, Kulonprogo area and Gunungkidul area. Both areas are located in Yogyakarta, Indonesia. As part of this KKN, our group was assigned in Hargotirto Village, Kulonprogo. Hargotirto Village itself has so many potencies, such as Gula Semut, Sekrasak Waterfall, Goat Farm, Fruit Commodities, and Coconut. In order to improve people’s creativity and its economic conditions, the utilization of coconut as oil is a great opportunity. The data was obtained by researching through the internet by the village’s website, journals, etc. The purpose of this journal is to provide informations on the utilization of one of the village’s potency, the coconut.